Phytochemical Screening, Proximate Composition and Mineral Element Analysis of Neocarya macrophylla (Gingerbread) Plum and its Effects on Microorganisms (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The need to increase the production and utilization of locally available food and antimicrobial resources has been discussed at different national and international forum. Fresh Neocarya macrophylla fruits were obtained from Birnin Kebbi central market in Kebbi state and it was transported to Biochemistry Department at Usmanu Danfodiyo University Sokoto, Sokoto State, Nigeria. Where the fruit of N. macrophylla was transformed or crushed through stigmasterol extraction with 70% of methanol. The compound, stigmasterol, indicated varying actions of antimicrobial activity against the microbes tested. Susceptibility test result showed inhibition ranging from 23 mm to 30 mm against all the organisms, which are S. aureus (24 mm), Salmonella Typhimurium (23 mm), P. aeruginosa (26 mm), E. coli (28 mm), Streptococcus pyogenes (25 mm), B. subitilis (23 mm), A. niger (29 mm), C. albicans (24 mm), and C. kruseii (23 mm). Creating zone of inhibition. The ash content was 6.70±0.05., moisture 14.23%±0.10., lipids 6.70% ±0.05., fibre 10.15%± 0.57., crude protein 1.015%±0.127., carbohydrate 51.33%±1.025. The pulp also contains low concentrations of magnesium (2.843±0.025) and very low concentrations of iron (0.0856±0.002), manganese (0.0122±0.048), copper (0.0087±0.002), and zinc (0.0024±0.001), which are important micro elements required by body for proper functioning. The result obtained indicate that Neocarya macrophylla fruit pulp of pharmaceutical and medical significances that are useful in Combating antibiotics resistance infections, nutritional rich in terms of minerals and carbohydrate composition.
Keywords: Antimicrobial; N. macrophylla; Minerals; Antibiotics; Antifungal